PENDAMPINGAN PEMBELAJARAN BAHASA ARAB DENGAN METODE MADARIJ BAGI MASYARAKAT DI KELURAHAN RAHMAH KOTA LUBUKLINGGAU - Rory Anugraha; Nurul Ahmad; Fevi Oktaria; Hapis Umam (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
Learning Arabic is a fundamental need for the Muslim community, particularly in deepening worship and understanding religious teachings. In Rahmah Village, Lubuklinggau City, most beginners in learning Arabic face challenges of time and limited access to education. This study focuses on the application of the Madarij method as an innovative solution that emphasizes a gradual and tiered approach to Arabic language learning. This study was conducted using a qualitative phenomenological approach through observation and interviews, and demonstrated a positive impact on language skills and student learning motivation. Through learning assistance at the mosque, this method has proven effective in improving the Arabic language skills of migrant workers, through repeated pressure (at-tikror) and habituation (at-ta'wid).